Biocatalysis, DNA–protein interactions, cytotoxicity and molecular docking of Cu(II), Ni(II), Zn(II) and V(IV) Schiff base complexes. (27th March 2017) - Balakrishnan, Chithiraivel; Theetharappan, M.; Kowsalya, P.; Natarajan, Satheesh; Neelakantan, M.A.; Mariappan, S.S.
Abstract : Four mononuclear metal complexes (Cu(II) (1 ), Ni(II) (2 ), Zn(II) (3 ) and V(IV) (4 )) were synthesized using the Schiff base ligand 2, 2′‐cyclohexane‐1, 2‐diylbis[nitrilo(1 E )eth‐1‐yl‐1‐ylidine]bis[5‐(prop‐2‐yn‐1‐yloxy)phenol] and structurally characterized by various spectral techniques. The catecholase‐mimicking activities of 1 –4 were investigated and the results reveal that all the complexes have ability to oxidize 3, 5‐di‐ tert ‐butylcatechol (3, 5‐DTBC) to 3, 5‐di‐ tert ‐butylquinone in aerobic conditions. Electrospray ionization mass spectrometry studies were performed for 1 –4 in the presence of 3, 5‐DTBC to determine the possible complex–substrate intermediates. X‐band electron paramagnetic resonance spectroscopy results indicate that the metal centres are involved in the catecholase activity. Ligand‐centred radical generation was further confirmed by density functional theory calculation. The phosphatase‐like activity of 1 –4 was investigated using 4‐nitrophenylphosphate as a model substrate. All the complexes exhibit excellent phosphatase activity in acetonitrile medium. The interactions of 1 –4 with calf thymus DNA (CT‐DNA) and bovine serum albumin (BSA) protein were investigated using absorption and fluorescence titration methods. All the complexes strongly interact with CT‐DNA and BSA protein. The complexes exhibit significant hydrolytic cleavage of supercoiled pUC19 DNA. Complexes 1 –4 exhibit significant in vitro cytotoxicity against MCF7 (human breast cancer) and MIA‐PA‐CA‐2 (human pancreatic cancer) cell lines. Moreover, the molecular docking technique was employed to determine the binding affinity with DNA and protein molecules. Abstract : Four mononuclear metal complexes containing a Schiff base ligand (2, 2'‐cyclohexane‐1, 2‐diylbis[nitrilo(1E)eth‐1‐yl‐1‐ylidine]bis[5‐(prop‐2‐yn‐1‐yloxy)phenol])] have been synthesized and characterized. Bio‐catalytic and DNA/protein interactions of these metal complexes were evaluated. In vitro cytotoxicity of metal complexes were studied against MCF7 and MIA‐PA‐CA‐2 cell lines.